viernes, 6 de julio de 2012

*9x2 + 6x + 10 =0

*3x2 - 9x =0

*-6x 2 + 10x =6

*x2 + 2x – 8 = 0

*4x2 + 12x – 8 = 0

a) x2 + 2x – 8 = 0
 a = 1   
 b = 2
 c = - 8 

  (x + 4 ) (x – 2) =0
  0 4 y –2 4 + -2 = 2
x + 4 = 0
x – 2 = 0

b)5x2-14x+8=0
a=5
b=-14
c=8

(5x-10)(5x-4)=0
5x1-10=0        5x2-4=0
5x1=10           5x2=4
5x1=10/5        x2=4/5
x1=2          


c)6x2-5x-6=0
a=6
b=-5
c=-6

6(6x2-5x-6)=0
36x2-5x(6)-36=0
(6x+4)(6x-9)=0

6x1+4=0         6x2-9=0
6x1=-4            6x2=9
x1=-4/6           x2=9/6
x1=-2/3           x2=3/2




No hay comentarios:

Publicar un comentario en la entrada